Guðmundr á Glasisvöllum: A Study of Potential Foreign Influences - Felix Lummer 1990- (2017)
This thesis aims to continue the scholarly debate on the potential Irish influence on the Guðmundr á Glasisvǫllum subject matter, which allows a careful comparison of the Irish and Old Norse data. The study will then bring into question whether Irish origins are more likely than a background in the Nordic culture. To do so, other material is considered that was largely omitted from the discussion about Guðmundr, Glasisvellir and Ódáinsakr to this day, namely past and present local folk tales of magical and vanishing islands found in both mainland Scandinavia (especially the so-called “Utrøst” legend in Norway) and the North Sea area (Faroe Islands, Iceland and Orkney). As will be shown, a Norwegian background seems most likely. It seems reasonable to interpret Ódáinsakr as a separate motif other rather than being intrinsically connected with accounts of Guðmundr. As this motif is found in both Irish and Old Norse literature, it can be suggested that Ódáinsakr has shared Christian origins. Þetta rannsóknarverkefni er ætlað sem framlag til frekari umræðu um hugsanleg írsk áhrif á efni Guðmundar á Glasisvǫllum til þess að gera samanburð á írskum og norrænum upplýsingum. Ritgerðin rannsaknar hvort írskur bakgrunnur sé líklegri en uppruni í norrænni menningu. Til að gera það eru ýmis gögn notuð sem hingað til hefur verið sleppt í umræðunni um Guðmundi, Glasisvǫllum og Ódáinsakri. Þessi gögn eru gamlar og nútímalegar þjóðsögur Skandinavíu (“Utrøst” í Noregi) og eyjanna í Atlantshafi (Færeyjar, Ísland, Orkneyjar) sem fjalla um yfirnáttúrulegar eyjar sem hverfa. Norskur bakgrunnur virðist vera líklegastur út af því að það er hægt að tulka Ódáinsakr sem óháð motif sem er ekki tengt við lýsingar Guðmundar. Þar sem mótifið er bæði til í írskum og norrænum bókmenntum er uppruni Ódáinsakrs sennilegt kristilegur.